Book Review. Racial Science and Human Diversity in Colonial Indonesia - Ruly Darmawan; Noeranti Andanwerti (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
This book which entitles ‘Racial Science and Human Diversity in Colonial Indonesia’ was written by Fenneke Sysling, a historian of science and Colonialism. This book is published in 2016 by NUS Press, National University of Singapore, Singapore. This book provides an exposure of Western thinkers, especially in the field of physical anthropology, in mapping out the existing races in Indonesia. Towards this mission, the Colonial scientists faced many obstacles in both technical and non-technical aspects.